RANCANG BANGUN KONTROL DAN MONITORING CONSTANT CURRENT REGULATOR MENGGUNAKAN MIKROKONTROLER DAN MODUL GSM VIA SMS GATEWAY - Hartono Hartono; Rifdian Indrianto Sudjoko; Slamet Hariyadi (Approach : Jurnal Teknologi Penerbangan, 2020)
Constant Current Regulator is a tool used for regulating the constant of current and the brightness of the visual aids of Airfield Ligtings. Currently there is no practical tool in the Aviation Polytechnics of Surabaya, so it is necessary to design a trainer Constant Current Regulators as a learning media.Therefore, it has been designed a miniature of Consatant Current Regulator using a microcontroller as the main component for controlling the current which is flowing in the load circuit.The measurement results of current sensors will provide data to the microcontroller for consideration if the current is appropriate with the predetermined reference current, if the measured current does not appropriate to the reference current, the microcontroller will control Solid-State Relay which serves as a switch to control current the load.Keywords: constant